Exploring racial/ethnic differences in substance use: a preliminary theory-based investigation with juvenile justice-involved youth - Mead Hilary K; Venner Kamilla L; Feldstein Ewing Sarah W; Bryan Angela D (BMC, 2011)
Abstract Background Racial/ethnic differences in representation, substance use, and its correlates may be linked to differential long-term health outcomes for justice-involved youth. Determining the nature of these differences is critical to informing more efficacious health prevention and intervention efforts. In this study, we employed a theory-based approach to evaluate the nature of these potential differences. Specifically, we hypothesized that (1) racial/ethnic minority youth would be comparatively overrepresented in the juvenile justice system, (2) the rates of substance use would be different across racial/ethnic groups, and (3) individual-level risk factors would be better predictors of substance use for Caucasian youth than for youth of other racial/ethnic groups. Methods To evaluate these hypotheses, we recruited a large, diverse sample of justice-involved youth in the southwest (N = 651; M age = 15.7, SD = 1.05, range = 14-18 years); 66% male; 41% Hispanic, 24% African American, 15% Caucasian, 11% American Indian/Alaska Native). All youth were queried about their substance use behavior (alcohol, marijuana, tobacco, illicit hard drug use) and individual-level risk factors (school involvement, employment, self-esteem, level of externalizing behaviors). Results As predicted, racial/ethnic minority youth were significantly overrepresented in the juvenile justice system. Additionally, Caucasian youth reported the greatest rates of substance use and substance-related individual-level risk factors. In contrast, African American youth showed the lowest rates for substance use and individual risk factors. Contrary to predictions, a racial/ethnic group by risk factor finding emerged for only one risk factor and one substance use category. Conclusions This research highlights the importance of more closely examining racial/ethnic differences in justice populations, as there are likely to be differing health needs, and subsequent treatment approaches, by racial/ethnic group for justice-involved youth. Additionally, this study highlights the need for timely, empirically supported (developmentally and cross-culturally) substance abuse interventions for all justice-involved youth.